Physical Activity in Adolescents Living in Rural and Urban New Caledonia: The Role of Socioenvironmental Factors and the Association With Weight Status - Wattelez, Guillaume; Frayon, Stéphane; Caillaud, Corinne; Galy, Olivier (Frontiers in Public Health, 2021)
Physical activity (PA) is an important factor for the prevention of overweight and obesity, particularly during adolescence. This study focuses on the understudied adolescent population of New Caledonia with the aim to (1) determine the daily PA levels and estimate the sedentary time through out-of-school sitting time; (2) highlight the influence of sociodemographic and environmental factors, and (3) assess the associations of PA and sitting time with overweight and obesity. A sample of 508 school-going adolescents living in New Caledonia was surveyed about their PA habits using the International Physical Activity Questionnaire–Short Form, as well as about the context in which they usually engage in PA. The influences of the place of living and ethnic community were also investigated. Results indicated that about 66% of the adolescents performed an average of at least 60 min of PA daily. Both Melanesian adolescent boys and girls were more active than Caucasian adolescents but only when they lived in rural areas (females: 115 vs. 93 min/day, p = 0.018; males: 133 vs. 97 min/day, p = 0.018). Indeed, PA was reduced in an urban environment (females: 88 min/day; males: 95 min/day, p = 0.028; rural vs. urban in Melanesian adolescents). Melanesian adolescents also spent less time in out-of-school sitting than Caucasian adolescents independently of where they lived (females: 164 vs. 295 min/day, p < 0.001; males: 167 vs. 239 min/day, p = 0.001). Feeling safe was positively associated with PA levels (females: ORadj = 2.85, p < 0.001; males: ORadj = 4.45, p < 0.001). In the adolescent boys, accessibility to a suitable place was also an important factor (ORadj = 2.94, p = 0.002). Finally, while PA and sitting time were negatively associated with overweight in male adolescents (ORadj = 0.28, p = 0.044 and ORadj = 0.39, p = 0.004), they were not in females. Living in a rural area allowed the Melanesian adolescents to maintain a more active lifestyle with more physical activities and less sitting time. Our results also indicated that safety was an important driver for engagement in PA. The urban environment in New Caledonia appears to be a contributor of a less active lifestyle in adolescents.